Kualitas Fisik Pupuk Cair (Biourine) Kambing Dengan Penambahan Berbagai Jenis Dekomposer Dalam Rangka Perbaikan Tanah Sebagai Media Tanam - Dwi Probowati Sulistyani; Adipati Napoleon; Yaswan Karimuddin; Sofia Sandi; Ida Aryani (xxxx-xxxx, 2020)
Sulistyani DP, Napoleon A, Karimuddin Y, Sandi S, Aryani I. 2020. Quality of physical properties of goat fertilizer (Biourine) with the addition of various types of decomposers to improve soil properties as a planting media. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The study aimed to identify physical qualities liquid fertilizer ( biourine ) goat by the addition of various types of decomposer.The materials used in the research areu urine goat, EM-4, banana excrescence  and feces goats. This study conducted in ekperimental with 4 treatment by 3 deuteronomy consisting of  PO(urine goats + mol banana excescence), P2(1 urine goat + mol feces goats), P3 (urin goats+  mol EM-4). Parameter that measured in research is the quality of the physical namely the odor  , pH , temperature and the color of the data obtained analyzed in deskriptip. The research results show that treatment of temperature at P0 34oC, treatment P1,  P2 and P3 of 32oC.Color biourine treatment P0 is reddishblack and P1, P2 and P3  is reddishblack, black concentrated. Odorbiourine goat  treatment P0 is very stinging and P1, P2,  and P3 is stinging. Ph around 7,67-8,29 . treatment.Conclusion is the banana mol  excrescence, mol feces goats and EM-4 can fix in soil as media plant.